A Better Version of Yourself: Sweat, Smiles and Muay Thai Tourism - Gonen,Max Yasmine (2019)
This ethnographic study investigates the functions of BestFighter Muay Thai and Mixed Martial Arts training camp in Koh Samui, Thailand, as a successful actor in a booming self-improvement economy. In this thesis I explore the entanglements with locality and power which enable what satisfied participants refer to as augmented experiences of self-improvement. Combining theoretical concepts such as Goffman’s frame analysis, Foucault’s care of the self, and critical masculinity studies, in this thesis I offer an analysis of the narratives and the practices that inform and construct the mythology of the training camp. The findings from my fieldwork indicate that participants largely thrive at BestFighter, finding self-discipline, meaningful friendships, and holistic balance. These benefits, however, are the end result of the complex interplay of socio-cultural factors including tourist imaginations of Thailand, the interstices of masculinity, sport and socialisation, and the way self-making processes are gendered and mythologized. This thesis analyzes not only why these (predominantly) men choose to spend their money and their holidays sweating and training intensely, but also how and why this type of holiday is framed as a transformational experience that always leaves participants at once satisfied and wanting more. Ultimately I argue that the success of the transformations enabled by BestFighter is due to the fact that it functions as a masculinity rehab: a place for men to enact simplified masculine archetypes incongruent with their everyday life.
Keywords: transformation; Muay Thai; self-improvement; tourism; Thailand; masculinity; sweat; experience economy; performance ethnography; MACA